Antibiotic prescribing practices of Filipino Dentists - Melchor A. Sarmiento; Mariano T Maglutac Jr; Ma. Susan Yanga-Mabunga (Intelektual Pustaka Media Utama, 2019)
There are reports that dentists overprescribe antibiotics which may contribute to antibiotic resistance. This is an exploratory study on antibiotic prescribing practices of Filipino dentists using an online platform to form a basis for antimicrobial stewardship policy for dentists. A link to an online questionnaire using Survey Monkey was posted in a Closed Group Facebook account of Filipino dentists. Two hundred thirty (230) dentists participated. Data was analyzed by Survey Monkey. Amoxicillin is the first choice of antibiotics(71.18%), andclindamycin is the second (57.27%). Most respondents follow the indications for antibiotic therapy, however, some will prescribe antibiotics for conditions without indications. For dental procedures, 88.99% will prescribe for periodontal surgery, 75.45% for endodontic surgery, 68.3% for extraction of a tooth with chronic infection, 87.17% for third molar surgery, 26.7% for routine endodontics, and 23.56% for periodontal treatment without surgery. Not all of the respondents would prescribe for medical conditions that require antibiotic prophylaxis, while 60.36% will prescribe when in doubt in diagnosis, under time pressure (25.68%), and 48.67% considers patient preference. Only 10.48% of the respondents are very familiar with antimicrobial stewardship, while majority (69.74%) have not attended a lecture for antimicrobial stewardship for dentists.There is inappropriate antibiotic prescribing of participants on certain dental diseases, procedures, and medical conditions. Most respondents are not very familiar and have not attended a lecture on antimicrobial stewardship for specifically for dentists.